A dynamic measure of divergence between two inactivity lifetime distributions. Issue 1 (2nd January 2022) - Mansourvar, Zahra
Abstract : This paper introduces a dynamic divergence measure to assess the discrepancy between the distribution functions of two inactivity lifetime random variables. Various time-dependent results on the proposed divergence measure in connection to other well-known measures in reliability engineering and survival studies are investigated. Some aging and monotonicity properties of such a measure are also studied. Furthermore, the proposed criterion is examined in two general classes of transformation models which results in some well-known models in the lifetime studies and survival analysis.